Ethinic Groups in Assam: A question of Identity - Borgohain, Mr.Anupom (International Journal of Psychosocial Rehabilitation, 2020)
Northeast India, comprising eight states, is a landlocked region and is surrounded by hills and mountains on three sides and the western side is bordered by plains. The region is located in the foothills of the Himalaya, the major part of which consist of the Arunachal Himalaya, the Mishimi and Miju hills, the Patkai hills, the Naga hills, the North Cachar hills, the Karbi hills, the Khasi hills, the Jaintia hills and the Garo hills. This vast foothill region is inhabitated by a large number of tribal and ethnic communities, such as Hrusso, Sherdukpens, Khowas, Apatanis, Nissis, Adis, Mishimis, Khamptis, Noctes, Wanchos, Khasis, Syntengs, Jaintias, Garos, Lushais, Kukis, Nagas, Mikirs, Singphos, Abors, Dafalas, Deuries, Karbis, Meitheis, Santhals etc. The different ethnic groups have been bearing varied and colourful customs and traditions, speaking different languages and dialects, many scholars consider it the melting pot of diverse races, castes, religions, languages and cultures. Inter-ethnic conflicts and struggle for identity among these ethnic groups too are not new but a frequently occurring phenomenon. However, such conflicts have become more common and all-pervading at present. It is to a great extent, due to over politicisation of the factors composing the ethnic identities. This paper tries to put in perspective the newly emerging patterns of ethnicity and demands for separate imaginary homelands in variegated paradigms and configurations.